Intonation contours and stress group patterns in declarative sentences of varying length in ASC Danish - supplementary data - Thorsen, Nina (Annual Report of the Institute of Phonetics University of Copenhagen, 1981)
Intonation contours in non-compound declarative sentences containing from one to eight stress groups were analysed with special regard to the manifestation of prosodic boundaries. The results are compared with a previous analysis of a very similar material. The neat and easy match between the prosodic and some of the major syntactic boundaries exhibited by the earlier corpus is not immediately replicated by the present utterances. Resetting of the intonation contour taken rigidly to manifest prosodic phrase group boundaries leads to counterintuitive phrase contours, but on the other hand, the alternative or supplementary boundary criterion suggested in the paper cannot be applied automatically and unambiguously. This strengthens the claim that in syntactically unambiguous non-compound sentences, prosodic structure does not directly reflect or map syntactic structure. However, the four speakers’ productions show a high degree of intra- as well as inter subject coherence, and the variation found in the intonation contours with varying sentence length is not random. Nevertheless, the principles governing the intonational properties, especially of the longer utterances, are not easily recovered, and it seems - maybe not surprisingly - that the semantic content of the (constituents of an) utterance must also be considered. The need for further research, also into the perception of prosodic structure, is evident.